Relational tensions in subgroup relationships : a case study of synchronous communication in a global virtual team - Chou, Chia-Yu (2015)
Studies about the positive influences of subgroups on global virtual team (GVT) functions are emerging in current literature (García & Cañado, 2011). However, the discoveries about the beneficial outcomes of subgroups are under-represented in comparison with the entries on subgroup hazards (Metiu, 2006). Few empirical studies in current literature explore the positive potentials of subgroups. This study probes subgroup relationships from a relational dialectic angle by employing the concept of face as relational connectedness and separatedness proposed in Face Constituting Theory (FCT). The goal of this study is to provide a unique angle to approach the existence of subgroups through exploring the relational negotiations in subgroup relationships. The research material of this study is the two teleconference recordings from a GVT within an international higher education consortium. Through analyzing the discourse of the meetings, this study provides an in-depth view of relational tensions among members in a team with different organizational affiliations. The findings reveal that both relational connectedness and relational separatedness among subgroups have positive influences on team functioning. The results suggest that allowing relational connectedness and separatedness to be involved and sustained according to the situation is a healthy phenomenon and needs to be seen as an integral part of subgroup relationships. The study concludes that subgroups should neither completely detach themselves from each other nor should they melt their perspectives fully. This conclusion enriches current understanding about the relational tensions residing in subgroup relationships and could provide implications for designing an effective GVT structure.